Sexual violence against Lesbian, gay, bisexual and transgender - Roviana Nurda Agustin (JHeS (Journal of Health Studies), 2022)
Sexual violence against lesbian, gay, bisexual, and transgender (LGBT) people is a public health problem that needs attention. It relates to the impact of physical, psychological, and social health including the risk of increasing cases of HIV/AIDS. The objective of this literature review is to identify the description of sexual violence against LGBT people. Search results on PubMed, ScienceDirect, and ProQuest found 527 articles associated with sexual violence against LGBT people. Seven articles met the inclusion criteria and were employed for this literature review. There were 5 themes which were discovered related to sexual violence against LGBT, encompassing the type and number of cases of sexual violence against LGBT; risk factors for sexual violence against LGBT people; perpetrators of sexual violence against LGBT; and the impact of sexual violence on LGBT people. In conclusion, cases of sexual violence against LGBT people tend to be higher than heterosexual groups. Sexual violence against LGBT is a complex problem and has an impact on the physical and mental health of victims. Thus, the implementation, utilization and success of programs related to the prevention and handling of sexual violence against LGBT groups need to be evaluated so that the program runs optimally.